The Relationship Between Motivation and Nurse Performance at Santa Elisabeth Hospital Medan 2024 - Tumanggor, Lili Suryani; Siallagan, Ance M.; Rostari Saragih, (Jurnal Midwifery, 2025)
Introduction Nurses have an important role in providing nursing services so that good and qual-ity performance is needed for patients, therefore high motivation is needed both from within and from outside which can generate enthusiasm in work by providing all abilities and skills in order to achieve goals and improve the quality of health services. This study aims to determine the relationship between Motivation and Nurse Performance at Santa Elisabeth Hospital Medan 2024. Method The design of this study uses a correlational design with a cross sectional ap-proach. The sampling technique uses a purposive sampling technique, with a sam-ple of 130 respondents. The measuring tool used is a questionnaire. Statistical analysis uses Chi-Square. Result The results of the study obtains high category work motivation are 81 respondents (62.3%) and nurses who have good performance as many as 87 respondents (66.9%). Conclusion It is hoped that nurses can further improve their motivation and performance in providing nursing services to patients.